THE STRUCTURE OF COLLOCATION AND ITS TRANSLATION STRUCTURES IN SUBTITLES OF KURZGESAGT YOUTUBE CHANNEL - Chyntia Veronika (Ma Chung Press, 2020)
This research aims to identify the types of English collocation and to investigate the structure of collocations in the Indonesian translation from English in Kurzgesagt YouTube Channel. This study used a descriptive qualitative method. The research used the theory of English collocation by McCarty and O’Dell (2008) and Indonesian collocation by Imran et al (2009) to identify English collocation types and investigate the structures of collocation in Indonesian. The research found that Adjective + Noun collocation types are mostly used to 133 of 232 and Verb + Noun to 45 or 19.40%. Focusing on structure of collocation translation equivalents in Indonesian, it was also found that Indonesian collocations 157 data or 67.7 % have the same structures and 75 data or 32.3% have different structures. 9 data or 3.9% are in the form of single words, and 1 data or 0.4% has no equivalent. After verification was made, Indonesian collocation equivalent are not always collocations: 90.5% are collocations and 9.5% are non-collocations, including single words. Based on the research finding, learners of English, translators, and future translators have to build awareness of the importance of collocation. The potential difficulties lie in the difference in translation equivalent.